The Effects of an APOE Promoter Polymorphism on Human Cortical Morphology during Nondemented Aging - Chen, Yaojing (J Neurosci, 2015)
Apolipoprotein E (APOE) is the best-known susceptibility gene for AD. It has been well demonstrated that the ε4 allele of the APOE gene can affect brain structure/function in nondemented individuals; however, other polymorphisms in the APOE gene have been largely overlooked when assessing the effects of APOE on the neural system. Rs405509 is a newly recognized AD-related polymorphism located in the APOE promoter region that can regulate the transcriptional activity of the APOE gene. To date, it remains unknown whether and how this APOE promoter polymorphism affects the human brain in aging. Here, for the first time, we investigate the effects of the rs405509 genotype (T/T vs G-allele) on human cortical morphology using a large cohort of nondemented elderly subjects (120 subjects in total; aged 52– 81 years). High-resolution structural MRI was performed; cortical thickness and surface area were analyzed separately. Intriguingly, nondemented carriers of the rs405509 T/T genotype showed an accelerated age-related reduction of thickness in the left parahippocampal gyrus compared with the G-allele carriers. Furthermore, the cortical thickness covariance between the left parahippocampal gyrus and left medial cortex, including the left medial superior frontal gyrus, supplementary motor area, and paracentral lobule, was modulated by the interaction of the rs405509 genotype and age. These novel findings suggest an important role for the APOE promoter polymorphism in the human brain and also provide valuable insights into how the rs405509 genotype shapes the neural system to modulate the risk of developing AD.